A comparison fo coping with coronary by-pass surgery between Lithuanian and West German patients - BIVEINYTĖ, SIMONA; LAURINAITIS, EUGENIJUS; UŽDAVINYS, GIEDRIUS (Psichologija, 1997)
The given study deals with a problem of coping of the coronary bypass surgery. The aim of this study is to contribute to the further identification of factors predicting poor emotional and related somatic adjustment after the surgery. The second aim of the study is to compare the forms of coping and the outcomes of coping between Lithuanian and West German patients. The level of anxiety, emotional stale and intensity of psychosomatic complaints were used as criteria for evaluating the effectiveness of coping processes. In the Vilnius University Heart Surgery Centre 114 patients undergoing coronary artery by-pass surgery were investigated using the Freiburger Questionnaire of Coping with Illness (Freiburger Fragebogen zur Krankheitsverarbeitung, FKV), the Giessener Questionnaire of Somatic Complaints (Der Giessener Beschwerdebogen, GBB), the State-Trait Anxiety Inventory (STAI), the mood inventory (Der Mehrdimensionaler Stimmungsfragebogen, MSF), the Centre for Epidemiological Studies Depression Scale (CESD), and the locus of control scale (Der Fragebogen zur Erfassung gesundheitsbezogener Kontrolueberzeugungen, FEGK). The first measurement using FKV, MSF, STAI, CES-D, GBB, and FEGK was made on the last day before surgery. The second measurement using MSF, STAI, and GBB was made during the forth to sixth day after surgery In the University Clinic in Frankfurt am Main 131 patients undergoing coronary artery by-pass surgery were investigated using the same procedure. The results were analysed using the means of SPSS/PC+. The Student test, Mann-Whitney test, and Wilcoxon test for uniformity of distributions, and Pearson correlation coefficient were the main methods of statistical analysis. The results support hypothesis that cognitive way of coping is the most favorable one in the heart bypass surgery situation Patients demonstrating cognitive avoidance before the surgery were significantly relieved in the forth to sixth day after the surgery. Patients demonstrating depressive way of coping showed the poorest emotional adjustment after the surgery (feelings of despair, anger and nervousness) and high intensity of somatoformic complaints. Patients demonstrating depressive way of coping and patients coping through social support seeking and hedonism showed many similar emotional and somatoformic characteristics after the surgery. Coping through trust and religiosity was associated with a stable and satisfactory emotional state before and after the surgery. Intensity of somatic complaints was positively associated with the level of anxiety preoperatively and postoperatively. All ways of coping were positively related with feelings of involvement, tiredness, concentration and physical exhaustion in the last day before the surgery. Anxiety as a trait predicted depressive way of coping and poor emotional adjustment preoperatively and postoperatively. The results strongly support the hypothesis that socio-economic and cultural living conditions influence the way of coping and its outcomes. German patients showed better emotional adjustment postoperatively.
Keywords: Lithuanian; German; coronary by-pass surgery; stress; coping